Gambling Despite Nationwide Self-Exclusion–A Survey in Online Gamblers in Sweden - Håkansson, Anders; Widinghoff, Carolina (Frontiers in Psychiatry, 2020)
Background: Voluntary self-exclusion is a well-known harm reduction intervention in problem gambling, although primarily in operator-specific or venue-based systems. A nationwide overall self-exclusion system (‘Spelpaus’) for all licensed gambling was introduced in Sweden in 2019. However, gambling in overseas companies despite national exclusion may be a concern in online gamblers. The present web survey study aimed to study self-reported self-exclusion and gambling despite exclusion in a nationwide multi-operator land-based/online exclusion system. Methods: Web survey in web panel members of a market survey company, carried out in May, 2020 (co-occurring with the COVID-19 pandemic). Past-year online gamblers (n=997) answered questions about gambling patterns, gambling problems, psychological distress, self-exclusion since ‘Spelpaus’ introduction, and gambling despite self-exclusion. Results: Seven percent reported ever self-excluded at Spelpaus, and this was associated with younger age, female gender, gambling problems, and chance-based games and online poker. In logistic regression, Spelpaus remained strongly associated with past-year online casino gambling, gambling problems, and absence of past-year sports betting. Among those having self-excluded, 38 percent reported gambling despite self-exclusion, most commonly online casino. Conclusions: In online gamblers in a setting with a nationwide self-exclusion system, using this was associated with past-year online casino gambling and gambling problems. Gambling despite self-exclusion appears to be common, and more commonly involves online casino. Stakeholders should aim to increase rates of self-exclusion in high-risk online gamblers, both during and beyond the COVID-19 situation in which the study was carried out. Also, policy makers should use gambling regulation in order to decrease the risk of breach self-exclusion online, such as through the prohibition of non-registered gambling operators. Further research should focus on in-depth analysis of the reasons for gamblers to enroll or not enroll in multi-operator self-exclusion.